STRENGTHENING THE LAW OF LAMPUNG LANGUAGE IN THE DIGITAL ERA: A STUDY OF THE DEPARTMENT OF EDUCATION AND CULTURE OF LAMPUNG PROVINCE - Lestari, Devi; Muhtadi, Muhtadi; Yusdianto, Yusdianto; Triyono, Agus (Law Faculty of Universitas Bandar Lampung, 2025)
Regional languages are an important part of cultural identity and objects of constitutional protection as regulated in Article 32 paragraph (2) of the 1945 Constitution. This study aims to analyze the challenges faced by the Lampung provincial government in efforts to preserve and strengthen the Lampung language in the digital era. The problem is studied how the government deals with social and technological dynamics in maintaining the existence of the Lampung language, especially through regional policies in the field of education. This study uses an empirical method. This study also uses the theory of Legal Politics and Regional Autonomy Theory. This theory is used to analyze the direction of the Lampung provincial government's legal policy and regional authority in strengthening the Lampung language as part of cultural affairs in the digital era. The results of the study show that the implementation of the Lampung language preservation policy still faces challenges, including limited digital learning media, minimal teaching staff, and minimal interest from the younger generation.